Peta Potensi Keagamaan Masyarakat Daerah Istimewa Yogyakarta - Moh Hasim (Analisa: Journal of Social Science and Religion, 2009)
Religious potential map of Daerah Istimewa Yogyakarta community has itsbackground on the need for having data which could describe diversity in thecommunity. These data, in general, are needed as material analyzes in understandingreligious sociology, as references in giving religious management, and as preliminearydata in arranging research plan. Data shown in Religipus Potential Map of Yogyakartainclude religious community composition, religious places, educational institutions,religious leaders and religious organizations. We notice from this religious potentialmap of Yogyakarta that Islam community in this area has quantitatively biggerpotential in almost of aspects namely education, religious organizations, followers,and human resources.Key words: Map, Religious Potential